MENGATASI MISKONSEPSI DINAMIKA DENGAN KONFLIK KOGNITIF MELALUI METODE DEMONSTRASI - Erawan Kurniadi (Jurnal Pendidikan, 2008)
This research  serves an analysis  on showing  and identifying the profile  of students'  misconception  on dynamics  materials  and its causes.  The  analysis  is also  set  to  measure  to  what  extent  is the students'    misconception    able  to be reduced   by making   use  of cognitive  conflict  under demonstration   method. The analysis  results in  conclusion    that  diagnostic   test  and  interview   catch  dynamic misconception.  Identified essential misconceptions  belong to 7 profile types  under  causes  which  are limited  by Newton  Law, the  wrong mathematic   formulation   for  Newton   Law.  Cognitive   learning   by demonstration    method  can  tentatively   reduce  the  misconception. Misconceptions   obtained  before cognitive  conflict  by demonstration method  are 91 % made by the students  of Physics,  and 60%  made by students  of mathematics.  After cognitive  conflict  learning  strategy, the misconceptions   can be reduced  to 36.5% and 14% repectiveJy.